Inhaled salbutamol and endurance cycling performance in non-asthmatic athletes - van Baak, M. A.; de Hon, O. M.; Hartgens, F.; Kuipers, H. (International Journal of Sports Medicine, 2004)
Beta2-adrenergic agonists are important therapeutic agents for the prevention and treatment of (exercise-induced) asthma in athletes, but may have ergogenic effects. In this study we investigated whether inhalation of a supra-therapeutic dose of 800 microgramm salbutamol before exercise affects endurance performance during a cycling trial in non-asthmatic athletes. In a double-blind, randomized cross-over study, 16 athletes performed two trials, where they had to perform a certain amount of work as fast as possible on a cycle ergometer, 30 minutes after inhalation of 800 microgramm salbutamol or placebo. Peak expiratory flow (PEF), forced vital capacity (FVC), and forced expiratory volume in 1 second (FEV1) were measured before and after exercise and blood samples were obtained before and during exercise. Cycling performance time was 4010.2 +/- 327.7 s after placebo inhalation and 3927.6 +/- 231.3 s after inhalation salbutamol (p < 0.05). Although salbutamol inhalation increased plasma free fatty acids, glycerol and lactate concentrations and decreased plasma potassium concentrations at rest, no differences between placebo and salbutamol in these variables were found during exercise. PEF and FEV1 were increased after salbutamol inhalation at rest compared with placebo, but the difference between placebo and salbutamol after exercise was no longer significant. Inhalation of a supratherapeutic dose of 800 microgramm salbutamol improved endurance cycling performance by 1.9 +/- 1.8 % in non-asthmatic athletes, which indicates that this route of administration does not exclude the possibility of an ergogenic effect of beta2-adrenergic agents in athletes. The increase in performance was not explained by changes in plasma concentrations of free fatty acids, glycerol, lactate, and potassium during exercise or by changes in ventilatory parameters at rest and after exercise. Therefore, the mechanism of the increase in performance remains to be determined.